Evaluation of university teaching styles in the virtual context - Olivera Carhuaz, Edith Soledad (2020)
The situation that is lived worldwide has promoted virtual education, so that university tea- chers have been forced to adapt to this exclusive way of teaching, therefore, questions ari- se about the didactics, methodology and resources they use in this environment to get stu- dents to learn. Given this phenomenon, the objective of the present study was to find out the predominant teaching styles among university teachers in a private institution in Lima. The methodology was descriptive of a quantitative approach and the sample was made up of 114 teachers from the Hospitality and Tourism faculty of the mentioned institution. The re- sults obtained determined that the prevailing teaching style is functional, followed by formal and structural. These styles are related to the academic knowledge of university teaching.